The Effect Of Motivation And Competence On Employee Performance With Commitment As An Intervening Variable At The Representative Office Of Bank Indonesia, West Sumatra - Bambang Pramono; Sri Rahayu; Saimara Sebayang (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the effect of motivation and competence on employee performance with commitment as an intervening variable at the Representative Office of Bank Indonesia, West Sumatra. The research method used is a quantitative approach with data collection techniques through questionnaires. The population in this study consisted of all employees totaling 60 people, using a saturated sampling technique, so that the entire population was used as respondents. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS software. The results of the study indicate that competence has a positive and significant effect on employee performance and also has a positive and significant effect on commitment. Commitment also has a positive and significant effect on employee performance. Meanwhile, motivation does not have a significant effect on employee performance, but has a positive and significant effect on commitment. In addition, commitment is proven to mediate the effect of competence and motivation on employee performance. Thus, improving employee performance can be achieved through enhancing competence and strengthening organizational commitment. The results of this study are expected to be taken into consideration by management in improving employee performance.